(3LGeY GdHjGf Yf JChjd Bi GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3JaSjQ ShQI GdMLQGJ Gdbhd ai JChjd bhdg YR hLd (B" (3jCjgG GdPjf BefhG dGJbOehG Hjf jOi Gddg (B" (3bGd CHh LYaQ jCjgG GdPjf CbQhG HhGMOGfjI Gddg s
(3BNQgG (B:s
(3jfJgi HJaSjQ GdBjI GdcQjeg (B" (3EP jZTi GdSOQI eG jZTi (B"[ (3ef ShQI GdfLe (B] (3Hbhdg (B: (3ZTjI GdedGFcI CeKGd GdZQHGf Mjf jbYf Yf GdTLQ bGd acdeI YfO Pdc abGd dg Sd Je GdSaQ HMeO Gddg s
(3jJVef JaSjQ ShQI GdMLQGJ Edi CKfGA ShQI GdfLes
(3cJHJ Ydi Qb ZRGds
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3gs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs